German Heart Report 2013 - Meinertz, Thomas; Diegeler, Anno; Stiller, Brigitte; Fleck, Eckart; Heinemann, Markus K.; Schmaltz, Achim A.; Vestweber, Martin; Bestehorn, Kurt; Beckmann, Andreas; Hamm, Christian; Cremer, Jochen (The Thoracic and Cardiovascular Surgeon, 2015)
Objectives The 25th German Heart Report provides a comprehensive analysis of morbidity and mortality in patients with selected heart diseases as well as services and care in cardiology and cardiac surgery in Germany during the period 2011–2012. It is the result of a multidisciplinary collaboration between the German Heart Foundation, the German Cardiac Society, the German Society for Thoracic and Cardiovascular Surgery, and the German Society of Pediatric Cardiology and is based on data from different sources. In addition, trends of the period from 1995 to 2012 are presented.Results The trends in morbidity due to cardiac diseases in 2010 and previous years continued in 2011. Compared with data from 1995 to 2010, one can observe:Compared with data from 2009, the mortality rates in 2011 differ somewhat; there is:These data are in agreement with findings from other Western countries. Coronary heart disease, the most frequent cardiac disease, has continuously decreased in frequency and mortality since 2000. The underlying reasons are discussed.Conclusion This report is an important resource for all parties of the healthcare system regarding heart disease conditions and their treatment in Germany.
Keywords: heart disease; morbidity; mortality; diagnostic; therapy procedures